Ethical Debates: Terrorism - Smith,David; Colvin, Madeleine; Smith, David (Kent Street Sydney Wayland, 2007)
Ethical Debates: Terrorism explores the complex ethical questions surrounding terrorism. It examines various perspectives, providing readers with a comprehensive understanding of the topic. The book delves into the history of terrorism, its causes, and the moral dilemmas it presents to societies worldwide. Key Themes Definition and Origins: Understanding what constitutes terrorism and its historical context. Causes and Motivations: Exploring the reasons behind terrorist acts and the motivations of those who commit them. Ethical Dilemmas: Analyzing the moral questions related to counter-terrorism measures, civil liberties, and the balance between security and freedom. This book serves as an educational resource for readers seeking to understand the multifaceted nature of terrorism and the ethical debates it engenders.